Shifting Lines of Force: Campus Carry and Power at The University of Texas at Austin - Albion M. Butters (European Journal of American Studies)
By passing “Campus Carry” law in 2015, the Texas state legislature made it legal for licensed adults to bring concealed handguns onto public university premises, including the classroom. The result was a cascade of shifting power dynamics, from the state’s “power over” the sanctum of the Ivory Tower to the university administration’s defiance of faculty and student protestors. In the classroom itself, preexisting mechanisms of power were contested and even inverted, with ideological fractures reflected in rhetoric and pedagogy. This paper employs mixed-methods ethnography to expose the multiple lines of force at UT Austin after the law was implemented and highlight the historical significance of this case for universities elsewhere in the United States where similar laws are planned or currently being passed.